Financial Skill in Enhancing Financial Resilience: A Bibliometric Analysis (2010-2025) - Sunandes, Aris; Handayati, Puji; Siswanto, Ely (Asian Journal of Management Analytics, 2025)
Small and medium enterprises (SMEs) are one of the key components that support a nation's economic resilience during a crisis, as they are able to survive by leveraging all their financial capabilities. This research aims to identify trend issues regarding the financial capacity of SMEs in facing financial resilience. A bibliometric analysis method is used to explore literature trends related to financial skills and financial resilience. A quantitative approach is applied with the assistance of VOSviewer tools for network visualization, co-occurrence analysis, and trend mapping. Financial resilience research has shifted from traditional approaches to a holistic paradigm that integrates digital, behavioral, and cultural aspects, emphasizing the need for a multidisciplinary approach. The analysis indicates a transition from static financial literacy models to dynamic frameworks influenced by technology and behavior. The rapid growth of digital finance topics reflects a transformative phase requiring agile policy and research responses. Further research should explore the relationships between emerging clusters to develop a more comprehensive financial resilience model in the digital era.